The effect of dietary L-carnitine on growth performance and tissue accretion rates in the early-weaned pig - K Q Owen; S A Blum; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 216 pigs (initially 11.7 Ib and 21 d of age) was used in a 35-weight, ancestry, and sex in a randomized complete block design, resulting in six pigs per pen (three barrows and three gilts) and six pens per treatment. Experimental diets were fed in two phases from d 0 to 35 postweaning. During Phase I (d 0 to 14 postweaning), the control diet was corn-soybean meal based; included 7.5% spray-dried porcine plasma, 25% dried whey, and 1.75% spray-dried blood meal; and was formulated to contain 1.6% lysine; and .44% methionine. On d 14, all pigs were switched to a Phase II (d 14 to 35 postweaning) diet that contained 10% dried whey and 2.5% spray-dried blood meal and was formulated to contain 1.25% lysine and .36% methionine. L-carnitine replaced corn in the Phase I and II control diets to provide dietary L-carnitine levels of 250, 500, 750, 1,000, and 1,250 ppm. On d 35, three barrows and three gilts per treatment (one pig per block) were slaughtered to determine carcass composition. From d 0 to 14 postweaning, increasing L-carnitine had no effect on growth performance. From d 14 to 35 and d 0 to 35, no differences occurred in average daily gain (ADG) and average daily feed intake (ADFI); however, pigs fed 1,000 ppm L-carnitine were more efficient (F/G) over the entire trial and were 1.94 lb heavier on d 35 than pigs on the positive control treatment. Plasma carnitine levels taken on day 14 increased as dietary carnitine increased. Percentage carcass CP, lipid, and daily protein accretion were not influenced by dietary L-carnitine on d 35. However, daily fat accretion was reduced, with pigs on the 750 ppm L-carnitine having the lowest daily fat accretion. Based on these results, L-carnitine addition reduces daily fat accretion and improves F/G when fed during the nursery phase.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Early-weaned pigs; L-carnitine; Growth; Pigs